Sejarah Perkembangan Kebudayaan Islam di Ogan Ilir, 1932-2004 - Ilhamudin Ilhamudin (JUSPI (Jurnal Sejarah Peradaban Islam), 2020)
The Ogan Ilir community is passionate about working together. The process of Islamization and development of Islam in Ogan Ilir was spread by Mr. Umar Baginda Saleh (1575-1600). Mr. Umar broadcasts Islam in the Tanjung Atap area. The jam and Pangeran Sido Ing Rajek, precisely Sakatiga Village. Sakatiga village as a refuge for Prince Sido Ing Rajek when the Dutch attacked and burned the Kuto Gawang Palace in 1659. Early in the 19th century there were several great scholars in Ogan Ilir, especially in Sakatiga. Among them are Kyai Bahri bin Bunga, Kyai Harun Sakatiga who has the title Sayyidina Harun, Kiai Ishak Bahsin. Period 1918-1942 Kyai Ishak Bahsin. In 1932 an Islamic Madrasa was established called Madrasah Nurul Islam Sribandung. In 1950 also officially established Sakatiga Raudhatul Ulum Islamic Boarding School which is one of the famous and famous pesantren among the people of the province of South Sumatra. Then on July 10, 1967 the Al-Ittifaqiah Upper Middle School (MMA) Madrasah was officially established in Indralaya, Culture in Ogan Ilir in the form of Islamic boarding schools / learning buildings for the students. in Ogan Ilir there are three oldest Islamic boarding schools namely Nurul Islam Islamic Boarding School in Sribandung, Raudhatul Ulum Islamic Boarding School in Sakatiga and Al-Ittifaqiah Islamic Boarding School in Indralaya. In addition there are several mosques built long ago including: Jami 'Darussholihin Mosque Meranjat Village, Al-Qubro Indralaya Mosque, and Al-Falah Mosque.Keywords: History, Islamic culture.